Strategi Penguatan Ekonomi Rumah Tangga Masyarakat Pedesaaan: Kajian Empiris Di Kecamatan Taebenu Kabupaten Kupang - K.T. Aman, Dominikus; Jehamat, Lazarus; Faah, Yuri Sandra (Papanda Publisher, 2024)
Poverty is a scourge on the lives of rural communities. Poverty gives birth to various social problems such as unemployment, school dropouts, malnutrition, crime and household problems such as child neglect and domestic violence. This research aims to describe the strategy of strengthening the household economy of rural communities. This type of research is a case study with a qualitative approach. This approach tries to portray a reality as holistic/whole, complex, dynamic, full of meaning and the relationship is interactive/reciprocal. The types of data used in this research are quantitative data and qualitative data. The data needed in this study were collected by means ofindepth interviews, observation, documentation. Qualitative data analysis. The qualitative analysis model referred to in this study is the model put forward by that qualitative analysis is a series consisting of three streams of activities that occur simultaneously, namely: Data Reduction, Data Presentation and Conclusion Drawing / Verification. The results of the study show that the human resources of the Taebenu sub-district community are one of the causes of the birth of rural poverty problems characterised by low levels of education and even most of the population does not attend school. However, on the other hand, the potential of agriculture and plantations in the Taebenu sub-district area is very promising such as rice, corn, beans; the availability of large agricultural and plantation land and livestock ownership. Government support in the form of the presence of Village-Owned Enterprises (BUMDes) is one solution that can encapsulate and provide solutions to the economic problems of rural communities, especially to maximise the available potential through empowerment.